La Muela de Cástulo (Provinz Jaén) und ihre Siedlungsphasen - Blázquez Martínez, José Maria; García-Gelabert, María Paz; López Pardo, Fernando (Madrider Mitteilungen, 2021)
Deutsche Zusammenfassung folgt.